2001
DOI: 10.1111/j.1095-8649.2001.tb02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Spring cannibalism on 1 year walleye pollock in the Doto area, northern Japan: is it density dependent?

Abstract: Cannibalism in walleye pollock off the eastern coast of the Hokkaido Island, Japan was important only during spring (April to June), and its importance increased from 0% in dry mass for <200 mm L S fish to 48·9% for >400 mm L S fish. Most of the prey was represented by age 1 year fish, showing a unimodal body size distribution with a mode at 121-130 mm. Although cannibal body size was larger in deeper (>150 m) water, there was no difference in prey size by depth, suggesting impingement of the predators inhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…There is a reason why the CF of small walleye pollock increased more rapidly than for large walleye pollock. In this survey area, because the distribution of small and large walleye pollock overlap during spring, cannibalism of walleye pollock occurred, and the minimum ratio cannibal/prey size was 1.74 (Yamamura et al. , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There is a reason why the CF of small walleye pollock increased more rapidly than for large walleye pollock. In this survey area, because the distribution of small and large walleye pollock overlap during spring, cannibalism of walleye pollock occurred, and the minimum ratio cannibal/prey size was 1.74 (Yamamura et al. , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Virtually all ages of pollock are cannibalistic. Juveniles, especially age‐0 pollock, thus need to segregate from adults to avoid predation; the wide continental shelves along the Doto coast offer refuges protected by thermal barriers (Yamamura et al. , 2001).…”
Section: Japan Pacific Population Of Walleye Pollockmentioning
confidence: 99%
“…In the 1990s, the incidence of heavy cannibalism was limited to the spring period in the Doto area (Yamamura et al 2001) -because strong stratification during summer and autumn offered juveniles thermal barriers against cannibalistic adults, and mesopelagic fishes and squids were important prey during winter (Yamamura et al 2002). The increased winter cannibalism observed in this study compensated for the lack of mesopelagic fishes and squids, which were absent from diets between 2001 and 2005.…”
Section: Changes In Major Preymentioning
confidence: 61%
“…8). Thus, summer cannibalism was more prevalent after a year with high recruitment, implying the potential to dampen interannual variations in recruitment (Yamamura et al 2001), whereas winter cannibalism showed only a non-significant negative correlation with recruitment. Reproductive success index (RPS) %Proportion of pollock in diets Fig.…”
Section: Implication For Population Dynamicsmentioning
confidence: 93%